A first measurement of electroweak production of a W boson in association with two jets with the ATLAS detector - King, RSB (2013)
A first measurement of Electroweak W + 2 jets production at high dijet mass is performed using sqrt(s) = 7 TeV pp collision data from the Atlas experiment corresponding to 4.6 fb−1 of integrated luminosity. The background only hypothesis is excluded with a significance of 4.89-σ. A cross section of σ = 325 ± 6 (lumi) ±32 (stat) +63−70(syst) ±86 (theo) fb is extracted in the fiducial region.